The citizen's perception of a shared responsibility during the COVID-19 management: Insights from a focus group study across four European countries. - L S Kengne Kamga; A C G Voordouw; M C De Vries; S Kemper; M P G Koopmans; A Timen (PLoS ONE)
Background The World Health Organisation emphasises the importance of a whole-of-society approach to the management of health emergencies, which includes a need to involve citizens. Yet, little guidance is found on how this should occur and, more importantly, the citizen's current perspective of their role. Understanding citizens' perceptions is the first step in preparing for citizen engagement during a future pandemic. Methods A qualitative research study of 16 focus groups comprising 89 participants was conducted in Finland, Slovenia, Spain, and the Netherlands. Four age-stratified focus groups in each country were organised online in the country's primary language. Inductive analysis of each focus group transcript was used to identify important themes that captured the participants' perceptions of their role in COVID-19 preparedness, response, and recovery. Results Three common themes were found in the cross-country analysis. The first theme was the citizen's personal involvement, with specific references to the citizen's responsibilities and their concrete actions during COVID-19 preparedness, response, and recovery. The second theme was that of the citizen as an information receiver, with specific references to the quantity and quality of the information received. The final theme was the relationship between the citizen and decision-makers, with specific references to the citizen's level of trust in the decision-maker, the decision-maker's communication style as perceived by the citizens, as well as the level of interaction between the citizens and decision-makers as perceived by the citizens. Conclusions Generally, citizens included in this study from Finland, the Netherlands, Slovenia, and Spain felt a shared responsibility in curbing the spread of the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) during the pandemic. However, they emphasised the imperative need to be better informed about the likelihood of, and the developments during a pandemic in their country. Furthermore, the quality of the information provision emerged as an important theme.